Dampak Model Pembelajaran Auditory, Intellektualy, Repatition (Air) Terhadap Minat Belajar Siswa - Reza Miftah Rizkiardi; Bambang Subali (INOPENDAS: Jurnal Ilmiah Kependidikan, 2018)
The purpose of this study was to determine the impact of the Auditory, Intellectualy, Repatition (AIR) learning model on the interest in learning science subjects in class III SDN 02 Banjaran. The background of this study was conducted to see whether there was an impact and change in the interest in learning science students in third grade SDN 02 Banjaran when the teacher used the Auditory, Intellectualy, Repatition (AIR) learning model. This type of research is descriptive qualitative research. The research method used is the survey method, the techniques used are interviews and observations. The results of the study based on interviews and observations of teachers and students showed the impact of changes in interest in learning science subjects in weather material and their influence on third grade students of SDN 02 Banjaran when teachers in learning use Auditory, Intellectualy, Repatition (AIR) learning models.